Rota Fortunae in the 1695 Kražiai Manuscript: The Literary Context and the Concept of the Work - Nedzinskaitė, Živilė (Senoji Lietuvos literatūra, 2020)
In 1695, eight Jesuit students guided by Professor Piotr Puzyna (1664–1717) wrote the manuscript Fructus horni meditationis rhetoricae (The Annual Harvest of Meditative Rhetoric), which is currently kept at The Princes Czartoryski Library in Cracow (sign. 1866 IV). This voluminous manuscript (692 pages) should be considered an important part of educative and rhetoric culture of the Jesuits in the Grand Duchy of Lithuania and a work that complements the mosaic of the Latin literature of Lithuania. It consists of prose (panegyric and persuasive speeches), poetry (long poems and cycles of various poetry genres), and pieces of poesis artificiosa. Although the smallest by volume (only 29 closing pages of the manuscript), the latter stands out in a number of works of pattern poetry. The paper is focused on one of them, ‘Rota Fortunae’: it provides the context of circle-shaped works in Poland and Lithuania and offers analysis of the conception and originality of the work contained in the Kražiai manuscript.Pattern poetry, which flourished in the Hellenistic epoch and at the time of the Carolingian dynasty, re-emerged in the Baroque epoch when published works of classical Greek and Medieval authors with examples of this poetry appeared in the sixteenth-seventeenth centuries, and when not only instructing and exhilarating but also surprising the reader became one of the key aims of literature. In Poland and Lithuania, pattern poetry appeared at the turn of the seventeenth century and became increasingly popular. The schools of the Society of Jesus, where collections of such poetry used to be collected and accumulated for pedagogical purposes, played an undisputed role in this. On the other hand, information on the structure of pattern poetry or its examples was rather scarce in the textbooks written by the Jesuit authors.Circle-shaped works are one of the varieties of pattern poetry. In the seventeenth century, they were most frequently related to the theme of Fortune, a volatile fate and the inevitable end. In Lithuania, the theme of the wheel of Fortune was known and quite popular, and although it was frequently seen in the small literary forms, none circle-shaped works of pattern poetry have been found in publications of the Grand Duchy of Lithuania so far. Still, extant manuscripts of lecture notes in poetics and rhetoric point to the popularity of circle-shaped works in the Baroque epoch. The examples found in them show that Jesuits schools taught their students to compose circle-shaped works. And although professors spoke of them more as a game or presented them as one of the possibilities to trigger surprise and admiration and to demonstrate one’s mastery in versification, circle-shaped works happened to encode deeper meanings related to the wheel of Fortune, while their complex composition enciphered a philosophical or theological layer.‘Rota Fortunae’, the circle-shaped work in the Kražiai manuscript composed by the Jesuit student Urban Alshut (1677–1748), is so far the only known original ‘wheel’ in the literature of the Grand Duchy of Lithuania. It is devoted to poverty (paupertas), one of the three Jesuit vows. The work consists of sixteen hexameter lines: eight of them are written in the spokes of the wheel and eight in the circle of the wheel. The Jesuit student produced a work of complex composition abounding in figures typical of artificial poetry (such as acrostic and telestich); he also demonstrated maturity of thinking and thought. Alshut’s work ingeniously links the secular treatment of the symbol of Fortune with the religious-meditative plane.What is important is that ‘Rota Fortunae’ of the Kražiai manuscript continues the traditions of artificial poetry cultivated by the Jesuits. In this case, Alshut’s work not only echoes the Jesuit circle-shaped works that feature Jesus’s monograms IHS in the centre, but points to the connection of the circle-shaped works with other figure compositions: mazes and the works in the shape of the sun (Iesus sol). Notably, the young poet both demonstrates his knowledge of the possibilities of the composition of pattern poetry and searches for new means of expression: in the centre of volatile life, he sees not Fortune and not Christ, but poverty, one of the vows that bring one closer to him.‘Rota Fortunae’ of the Kražiai manuscript signifies the Jesuits’ attention to all forms of literature: a small work of just sixteen lines encompasses a large cultural and semantic, secular and religious load that reflects the rich literary tradition of the Grand Duchy of Lithuania.
Keywords: Society of Jesus; Kražiai; pattern poetry; rota Fortunae; Latin literature of the Grand Duchy of Lithuania; poetics; rhetoric